2019
DOI: 10.1177/0021998319876684
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and investigation on the properties of ilmenite (FeTiO3)-based Al composite by accumulative roll bonding

Abstract: In the present study, the aluminum (Al) 1050–FeTiO3 composite was fabricated through accumulative roll bonding process, and the resultant mechanical properties were evaluated at different deformation cycles at ambient temperature. The effect of the addition of FeTiO3 particle on the microstructural evolution and mechanical properties of the composite during accumulative roll bonding was investigated. The Al–2, 4, and 8 vol.% FeTiO3 composites were produced by accumulative roll bonding at room temperature. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Among these natural minerals, India is the 2nd largest country for ilmenite (FeTiO 3 ) mining (∼348MT per year). 18,19 Rasidhar et al 20 and Elwan et al . 19 reported that the addition of ilmenite into the aluminum alloy enhanced the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these natural minerals, India is the 2nd largest country for ilmenite (FeTiO 3 ) mining (∼348MT per year). 18,19 Rasidhar et al 20 and Elwan et al . 19 reported that the addition of ilmenite into the aluminum alloy enhanced the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the natural minerals viz. sillimanite, 10 ilmenite, 11 garnet, 12 zircon, 13 and rutile 14 are preferred over synthetic ceramics. Kumar et al 15 observed that the addition of 2–6 wt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some reports, the increment of roughness increases the wear and corrosion rate of materials. [35][36][37] Characterization of nanocomposites is highly important in the implementation of nanocomposite studies for ensuring the successful manufacturing of these kinds of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Powder metallurgy, stir casting method [3][4][5][6][7][8][9][10], accumulative roll bonding (ARB) method [11][12][13][14][15][16][17][18] were utilized to prepare the aluminum matrix with different reinforced composite. From the results, it is identified that the mechanical properties obtained from both methods exhibit the improved properties of the composites.…”
mentioning
confidence: 99%